Manfaat Media Gambar pada Pembelajaran Menulis Deskripsi Peserta Didik SD IT an-Nahl - Nurjani, Nurjani; Safrizal, Safrizal (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The research aimed at how to use image media in learning to write descriptions of students at SD IT An-Nahl Aceh Tengah. The research was conducted using descriptive qualitative research. The data used in this study are primary and secondary data. Data collection techniques in the from of conducting interviews an observations, interviews werw conducting with school principals, third and fourth grade educators at IT An-Nahl Aceh Tengah Elementary School, then with third and fourth grade students at IT An-Nahl Aceh Tengah Elementary School. The results of this study are the use of media images in learning to write descriptions for both educators and studnts in the low and high classes of SD IT An-Nahl Aceh Tengah. Educators feel that existence of media image helps in explaining learning to students, because educators can provide various questions based on the evailable images, and will help students express ideas in writing. The students also feel motivated by the emergence of a sense of pleasure within them in participating in learning, because the media used by educators has a variety of colors and characters, so that makes them happy in learning.